Optimization of molecular distillation to concentrate ethyl esters of eicosapentaenoic (20:5 ω-3) and docosahexaenoic acids (22:6 ω-3) using simplified phenomenological modeling - Rossi, Pablo Cesar (2011)
Squid oil contains high concentration of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The purpose of this work was to optimize the process of separation by molecular distillation of ω-3 fatty acid ethyl esters obtained from squid oil. The separation process was conducted in two stages in a laboratory-scale molecular distiller. A mathematical model based on the mass transfer phenomena was developed. The Nelder-Mead numerical method was used to optimize the model. RESULTS: The ω-3 content in the output material of the stage II increased with the temperature of stage I (T 1). The amount of distillated material in stage I increased and the distillated material in the stage II decreased with the increment of T 1. That implied a decreasing of the ω-3 recovery in the distillated material in the stage II. In addition, the ω-3 recovery increased with the temperature of stage II (T 2), but the temperatures should be less than 140 °C to avoid chemical changes. The optimization results showed an optimal process at T 1 = 120.5 °C and T 2 = 140 °C. CONCLUSION: The theoretical model and the optimization give decision criteria about the operative conditions for reaching the highest yield during molecular distillation of ω-3 fatty acid ethyl esters. © 2011 Society of Chemical Industry.